Ernst Caramelle : Forty Found Fakes 1976-1978. (New York : Thomas Way & Company, 1979)
A collection of found newspaper clippings that resemble works by some of Caramelle's contemporaries, including Daniel Buren, Panamarenko, Duane Hanson, Christo, ...
Acconci, Vito ; Arman ; Becher, Bernd & Hilla ; Beuys, Joseph ; Boltanski, Christian ; Broodthaers, Marcel ; Brown, Trisha ; Burden, Chris ; Buren, Daniel ; Caramelle, Ernst ; Christo ; Darboven, Hanne ; Feldmann, Hans-Peter ; Fluxus ; Fulton, Hamish ; Gac, Jean Le ; Gibson, Ralph ; Gironcoli, Bruno ; Haacke, Hans ; Hanson, Duane ; Heizer, Michael ; Judd, Donald ; Kaprow, Allan ; Kosuth, Joseph ; Kriwet, Ferdinand ; Lakner, Laszlo ; Lichtenstein, Roy ; Long, Richard ; de Maria, Walter ; Muntadas, Antoni ; Nitsch, Hermann ; Paik, Nam June ; Palermo, Blinky ; Panamarenko ; Petzold, Friedericke ; Poirier, Anne & Patrick ; Richter, Gerhard ; Rinke, Klaus ; Serra, Richard ; Vostell, Wolf ; Wewerka, Stefan
Engels & Duits
boek